Social representations of people with diabetes regarding their perception of family support for the treatment - Santos, Manoel Antônio dos; Alves, Roberta Cancella Pinheiro; Oliveira, Valmir Aparecido de; Ribas, Camila Rezende Pimentel; Teixeira, Carla Regina de Souza; Zanetti, Maria Lúcia (Revista da Escola de Enfermagem da USP, 2011)
The objective of this qualitative study was to identify the social representations that people with diabetes have on their perception of family support for the treatment. The Theory of Social Representations was used as the theoretical and methodological framework. Participants were 41 people with diabetes assisted at a university in the state of São Paulo in 2007. The focal group strategy was used for data collection, and thematic content analysis was performed. Results revealed three categories: family support is present in the everyday life of people with diabetes; the family does not always support the person with diabetes in his or her needs; the person with diabetes assumes the responsibility to trigger family support. Participants see family support as a relevant factor for the treatment, but they also point out that excessive control from relatives limits their autonomy and originates ambiguous feelings. The multiprofessional team must take into consideration that knowing social representations helps improve the health care delivered to people with diabetes.